A 3D-printed hybrid vertebroplasty, kyphoplasty and screw augmentation teaching model simulating high and low bone mineral densities - Jeising, Sebastian; Köber, Sabrina; Staub-Bartelt, Franziska; Beez, Thomas; Sabel, Michael; Ahmadi, Sebastian A. (Brain and Spine, 2026)
Introduction: Vertebral fractures are highly prevalent, particularly among the elderly and patients with osteoporosis. Current surgical training for vertebral augmentation procedures is largely confined to the operating room, where opportunities are inherently limited in both duration and scope. Research question: To develop a realistic, accessible, and cost-efficient hybrid training model for fluoroscopy-guided vertebroplasty, kyphoplasty, and pedicle screw augmentation, replicating both high- and low-density vertebral bone. Material and methods: Additive manufacturing techniques were applied to reproduce vertebral morphology, bone matrix characteristics, and radiopacity corresponding to varying bone mineral densities. Fluoroscopic guidance and subsequent CT imaging were used to evaluate cement distribution and procedural realism. A structured user assessment was conducted to rate anatomical accuracy, tactile feedback, and educational value. Results: Two printing protocols were optimized to closely replicate the radiographic and haptic properties of vertebrae with high and low bone density. CT imaging confirmed realistic cement dispersion within the printed vertebral structures. User evaluations rated the model as excellent for anatomical accuracy and educational value, and very good for tactile realism. Discussion and conclusion: This 3D-printed hybrid model provides a cost-effective and reproducible platform that closely simulates both the technical and radiographic aspects of vertebroplasty, kyphoplasty, and pedicle screw augmentation. This novel tool offers advanced training opportunities and enhances the comprehension of intraoperative spinal anatomy at a fraction of the cost of commercially available kits.
CRIS-Team Scopus Importer:2026-03-20
Keywords: 3D printing; Kyphoplasty; Osteoporosis; Pedicle screws; Surgical education; Vertebroplasty